Ischemic burden and clinical outcome: is one ‘culprit’ ischemic segment by dobutamine stress magnetic resonance predictive? - Giusca, Sorin; Buß, Sebastian Johannes; Katus, Hugo; Korosoglou, Grigorios (PLOS ONE, 2014)
Aims: We sought to evaluate the impact of ischemic burden for the prediction of hard cardiac events (cardiac death or nonfatal myocardial infarction) in patients with known or suspected CAD who undergo dobutamine stress cardiac magnetic resonance imaging (DCMR). Methods: We included 3166 patients (pts.), mean age 63±12 years, 27% female, who underwent DCMR in 3 tertiary cardiac centres (University Hospital Heildelberg, German Heart Institute and Kings College London). Pts. were separated in groups based on the number of ischemic segments by wall motion abnormalities (WMA) as follows: 1. no ischemic segment, 2. one ischemic segment, 3. two ischemic segments and 4. ≥three ischemic segments. Cardiac death and nonfatal myocardial infarction were registered as hard cardiac events. Pts. with an “early” revascularization procedure (in the first three months after DCMR) were not included in the final survival analysis. Results: Pts. were followed for a median of 3.1 years (iqr 2-4.5 years). 187 (5.9%) pts. experienced hard cardiac events. 2349 (74.2%) had no inducible ischemia, 189 (6%) had ischemia in 1 segment, 292 (9.2%) in 2 segments and 336 (10.6%) ≥3 segments. Patients with only 1 ischemic segment showed a high rate of hard cardiac events of ∼6% annually, which was 10-fold higher compared to those without ischemia (0.6% annually, p<0.001) but similar to those with 2 and ≥3ischemic segments (∼5.5% and ∼7%, p = NS). Conclusions: The presence of inducible ischemia even in a single ‘culprit’ myocardial segment during DCMR is enough to predict hard cardiac events in patients with known or suspected CAD.
Gesehen am 19.10.2020